2022
DOI: 10.1021/acsami.2c01251
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Output Performance of Triboelectric Nanogenerator by Switchable Stimuli in Metal–Organic Frameworks for Photocatalysis

Abstract: Precise control of the structure of crystalline materials is an efficient strategy to manipulate the fundamental performance of solids. In metal−organic framework (MOF) materials, this control can be realized by reversible cation-exchange through chemically driven changes in the crystalline state. Herein, we reported that the reversible structural transformations between an anionic Zn-MOF (1) and a topologically equivalent bimetallic Zn/Co-MOF (2) were accomplished. Both MOFs powders and their hybrid composite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 65 publications
(95 reference statements)
0
23
0
Order By: Relevance
“…Meanwhile, the average bond length of Co–N is about 1.97 Å, suggesting high-strength coordination bonds and good thermodynamical stability. 37 The percentage of the total solvent-accessible volume of JNU-207 was calculated to be 31.7% using the PLATON software. To evaluate the valence of the Co species in JNU-207 , X-ray photoelectron spectroscopy (XPS) experiments were performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the average bond length of Co–N is about 1.97 Å, suggesting high-strength coordination bonds and good thermodynamical stability. 37 The percentage of the total solvent-accessible volume of JNU-207 was calculated to be 31.7% using the PLATON software. To evaluate the valence of the Co species in JNU-207 , X-ray photoelectron spectroscopy (XPS) experiments were performed.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with ligand modification and photocatalyst encapsulation, the tuning of metal nodes (clusters) to improve the catalytic activity of MOFs has been less studied in recent years [33][34][35][36] The integration of cobalt metal has been demonstrated to increase the electron-transfer efficiency and improve the photocatalytic performance. 19,[37][38][39] Thus, we envisioned that combining the above-mentioned D-A-D ligand and cobalt cluster could lead to a chemically stable heterogeneous photocatalyst with a wider light-absorption range, and an enhanced charge-transfer efficiency as well as a boosted ROS generation efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the friction layer readily adhered to the PVDF layer because Cd­(NO 3 ) 2 ·4H 2 O absorbed water and was deliquescent during the friction process (Figure S10c,d). Therefore, we speculated that the central Cd atom, acting as a node to link the H 2 BBPD and bipyridyl-terminated ligands, formed a well-defined platform to easily transfer electrons, in agreement with previous reports, through cation-exchange-induced reversible single-crystal-to-single-crystal structural transformations. , …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we speculated that the central Cd atom, acting as a node to link the H 2 BBPD and bipyridyl-terminated ligands, formed a well-defined platform to easily transfer electrons, in agreement with previous reports, through cationexchange-induced reversible single-crystal-to-single-crystal structural transformations. 60,61 Having obtained the order of experimental electron-losing capability of the bipyridyl-terminated bridging ligands in the hierarchical frameworks of Cd-CP-based 1−3, we conducted DFT calculations to gain a deeper insight into the influence of the electron escape possibility on the bridging ligands at the atomic level. The calculated results showed that the highest occupied molecular orbital (HOMO) of bridging ligands in hierarchical frameworks Cd-CP 1−3 is located at the coordination O and N atoms, with matching HOMO energies of −0.0413, −0.0503, and −0.0425 a.u.…”
Section: Resultsmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs), engineered with metal ions/clusters and organic ligands using reticular chemistry, have emerged as modularly structured molecular compositions with enabling regulation of their physicochemical functions. Because of their reticular nature with functional active sites and well-defined platforms, MOFs were ideal molecule catalysts with adjacent and isolated sites available as cooperative and single-site catalysts to realize a series of chemical transformations. Meanwhile, benefiting from their tailorable structural transformations of MOFs, unlike classical porous materials, the coordination microenvironments and valence states of active sites could be tuned accurately to obtain site-selective reactions by the postsynthetic modification (e.g., dissolution-recrystallization or the single-crystal to single-crystal (SC-SC)) technique through solid–gas/liquid phase processes. ,,, These processes provided a suitable approach to adjust the nature of the active sites and their space structures with periodic azimuths and distances, thereby allowing further control of their catalytic activity to achieve true “turn-on/off” processes for similar functional groups with different reaction paths. ,,, Therefore, for the sustainable employment of MOFs in real systems, rational synthetic tactics were needed to regulate the atomically precise active sites in MOFs and endow them with predictable ways to control site-selective reactions.…”
Section: Introductionmentioning
confidence: 99%